PWE-035 Early experience of pancreatoscopy-directed electrohydraulic lithotripsy for pancreatic ductal stones in painful chronic pancreatitis. (22nd June 2015) - Bekkali, N; Murray, S; Johnson, G; Chapman, M; Pereira, S; Webster, G
Abstract : Introduction: Painful chronic pancreatitis is often associated with main duct obstruction due to stones. Approaches to management are challenging, including surgery, extracorporeal shock wave lithotripsy (ESWL), or endoscopic approaches. All have their limitations. Electrohydraulic lithotripsy (EHL) using Spyglass™ directed visualisation is highly effective for treating difficult bile duct stones, and is increasingly used in the UK. Here we report our early experience of Spyglass ™ pancreatoscopy and EHL for pancreatic duct stones. Method: We retrospectively audited our unit's use of Spyglass™ EHL in the period February 2013–February 2015, with a focus on those patients undergoing pancreatic EHL. Indication, procedural details, and clinical outcome were assessed. Results: Eighty-five procedures for Spyglass™ and EHL for stones were performed, of which 5 (6%) were carried out for pancreatic stones in 4 patients (3 female, mean age 46 years ±16 years). All patients had painful chronic pancreatitis, with radiological evidence of a dilated pancreatic duct, and main duct stone disease within 2 cm of the ampulla. Surgical options had been considered in all cases. Prior to EHL all patients had undergone pancreatic sphincterotomy and pancreatic duct stenting. Stone fragmentation and duct decompression was achieved in 75% (3/4) of cases. One patient required two EHL procedures to achieve clearance. In the patient with failed clearance, pancreatoscopy revealed that the stone was not in the main duct, but in the adjacent parenchyme. There were no procedure related complications. All patients with successful EHL had pain relief/marked improvement at clinical review (mean follow up - 6.8 ± 5 months). Conclusion: Pancreatoscopy with EHL may have a valuable role in treating obstructing pancreatic duct stones, possibly avoiding the need for surgery in some patients. However, careful patient selection is mandatory, and more studies are needed to better define treatment approaches. Disclosure of interest: None Declared.